P708 Prospective study to predict psychological morbidity in young people with inflammatory bowel disease using novel risk assessment tool. (25th January 2019) - Hoogkamer, A; Brooks, A; Rowse, G; Norman, P; Lobo, A
Abstract: Background: Psychological morbidity in inflammatory bowel disease (IBD) is common with a reported prevalence of up to 50% and far reaching impact on quality of life as well as on education and employment. Young people living with IBD face the additional challenge of being at a pivotal point in their development. Prediction of future development of psychological morbidity in young people with IBD would identify those at greatest risk and enable early intervention. The aim of this study was to identify risk factors which predict psychological morbidity in young people aged 16–24 years using a novel risk assessment tool (IBD-RAPID). Methods: Patients were recruited to a questionnaire-based study either online or face-to-face from outpatient services. Measures of anxiety and depression (HADS), IBD specific health-related quality of life (IBDQ) and the IBD-RAPID were made at baseline (T1) and at 6-months (T2). Correlations were identified between baseline factors and outcome measures of anxiety, depression and health-related quality of life (HRQoL) at T2. Regression analysis identified T1 items predictive of the development of each outcome. Sensitivity and specificity analysis was performed to identify the strength of the models when accounting for age, gender and baseline psychological morbidity. Results: 132 participants were recruited either online or in clinic and completed IBD-RAPID and outcome measures at T1 (median age 21 years, 65.9% female). High levels of psychological morbidity at T1 were identified: anxiety ( n = 76/112, 67.9%), depression ( n = 38/113, 33.6%), and impaired HRQoL ( n = 115/125, 92%). Self-harm ( n = 30/132, 22.7%) and suicidal ideation ( n = 24/131, 18.3%) were reported at T1. N = 49/132 (37.1%) of participants completed IBD-RAPID at T2, with significant differences at baseline between completers and non-completers. Regression analysis controlled for baseline age, gender and psychological morbidity. Living with a stoma predicted development of depression ( f 2 = 0.60) and feelings of sadness/hopelessness combined with impaired well-being predicted the development of a lower health-related quality of life ( f 2 = 0.42). Impaired well-being predicted the development of anxiety when taking sample size into account ( f 2 = 0.31). Conclusions: IBD-RAPID is a novel tool to predict psychological morbidity in young people with IBD. In this first prospective study in this cohort, key risk factors for development of anxiety, depression and lower HRQoL have been identified – but also a high attrition rate. These findings can be incorporated into current practice and provide the basis for optimising further validation studies and their design.